Agronomic and Biochemical Responses of Sunflower under Integrated Nutrient Management and its Residual Effects on Fodder Cowpea - Kundu, Rajib; De, Chandan; Ali, Takbir; Brahmachari, Koushik; Poddar, Ratneswar; Moinuddin , Golam; Maity, Prabaha (International Journal of Bio-resource and Stress Management, 2026)
A two-year field study was carried out during January–April and May–June of 2022 and 2023 at Uttar Chandamari village, Nadia district, West Bengal, India to evaluate the impact of integrated nutrient management (INM) on the agronomical and biochemical characteristics of sunflower (Helianthus annuus L.) and its residual effects on a subsequent fodder cowpea (Vigna unguiculata L.) crop. The study comprised nine nutrient management treatments combining varying proportions of inorganic fertilizers with organic sources, arranged in a randomized block design with three replications. Application of 100% recommended dose of fertilizer (RDF) through inorganic fertilizers achieved the highest sunflower growth, seed yield and nutrient uptake. However, the integrated treatment receiving 75% RDF through chemical fertilizers and 25% recommended dose of nitrogen (RDN) through vermicompost performed comparably while enhancing soil nutrient status and seed quality attributes. Sole organic treatments produced lower sunflower yields but significantly enhanced oil content and oleic acid composition. Residual effects were pronounced in fodder cowpea, with the highest fodder yield and nutrient uptake observed under 100% RDN through vermicompost in previous crop. Economically, the application of 100% RDF through inorganic fertilizers resulted in the maximum net returns and benefit-cost ratio, closely followed by partial substitution of inorganic nitrogen with vermicompost. The findings underscored the agronomic and environmental advantages of integrated nutrient management strategies, recommending the combination of 75% RDF from inorganic source with 25% RDN through vermicompost as the most balanced approach for enhancing system productivity and soil health in intensive cropping systems of Eastern India.